Improved Anticancer Photothermal Therapy Using the Bystander Effect Enhanced by Antiarrhythmic Peptide Conjugated Dopamine‐Modified Reduced Graphene Oxide Nanocomposite. Issue 2 (8th November 2016) - Yu, Jiantao; Lin, Yu‐Hsin; Yang, Lingyan; Huang, Chih‐Ching; Chen, Liliang; Wang, Wen‐Cheng; Chen, Guan‐Wen; Yan, Junyan; Sawettanun, Saranta; Lin, Chia‐Hua
Abstract : Despite tremendous efforts toward developing novel near‐infrared (NIR)‐absorbing nanomaterials, improvement in therapeutic efficiency remains a formidable challenge in photothermal cancer therapy. This study aims to synthesize a specific peptide conjugated polydopamine‐modified reduced graphene oxide (pDA/rGO) nanocomposite that promotes the bystander effect to facilitate cancer treatment using NIR‐activated photothermal therapy. To prepare a nanoplatform capable of promoting the bystander effect in cancer cells, we immobilized antiarrhythmic peptide 10 (AAP10) on the surface of dopamine‐modified rGO (AAP10‐pDA/rGO). Our AAP10‐pDA/rGO could promote the bystander effect by increasing the expression of connexin 43 protein in MCF‐7 breast‐cancer cells. Because of its tremendous ability to absorb NIR absorption, AAP10‐pDA/rGO offers a high photothermal effect under NIR irradiation. This leads to a massive death of MCF‐7 cells via the bystander effect. Using tumor‐bearing mice as the model, it is found that NIR radiation effectively ablates breast tumor in the presence of AAP10‐pDA/rGO and inhibits tumor growth by ≈100%. Therefore, this research integrates the bystander and photothermal effects into a single nanoplatform in order to facilitate an efficient photothermal therapy. Furthermore, our AAP10‐pDA/rGO, which exhibits both hyperthermia and the bystander effect, can prevent breast‐cancer recurrence and, therefore, has great potential for future clinical and research applications. Abstract : In vitro and in vivo models are used to explore the therapeutic effect in human cancer cells exposed to NIR‐irradiated antiarrhythmic peptide 10 on the surface of dopamine‐modified reduced graphene oxide (AAP10‐pDA/rGO). The AAP10‐pDA/rGO nanoplatform, which exhibits both hyperthermia and the bystander effect, can facilitate the photothermal cancer treatment and prevent cancer recurrence. The findings of this study offer a better understanding of the design of graphene‐based nanocomposites for cancer photothermal therapy.